New crystallographic data and formula revision of phuralumite, Al2[(UO2)3(PO4)2O(OH)](OH)3(H2O)9 - Dal Bo,F.; Hatert,F.; Philippo,S. (Journal of Geosciences, 2017)
The crystal structure of phuralumite, Al2[(UO2)3(PO4)2O(OH)](OH)3(H2O)9, from the Kobokobo pegmatite (Kivu, Democratic Republic of Congo), was refined from single crystal X-ray diffraction data. Four samples have been investigated in this study, and the crystal structure was to R1 = 0.0566, 0.0544, 0.0661 and 0.0353, for 5739, 5953, 6007 and 5793 unique observed reflections, for the samples VC2048, VC2048, VC2054 and VC2055, respectively. Phuralumite is monoclinic, space group P21/n, a = 9.4407(3), b = 20.8596(8), c = 13.4326(4) Å, β = 107.905(4)°, V = 2517.40(17) Å3, and Z = 4 (sample VC2048). The structure consists of [(UO2)3(PO4)2O(OH)]3- layers, parallel to (010), which are connected by Al3+ ions and H2O molecules. The uranyl phosphate sheets show the phosphuranylite anion topology, while the Al3+ ions occur in 5- and 6-fold coordination and are connected together to form Al4O4(OH)6(H2O)4 clusters. The crystallographic data obtained from the four structural models converge and confirm the previously determined structure for phuralumite. However, these new data also show some discrepancies in the bond-valence analysis, especially in the assignment of the OH- groups and water molecules. As a consequence of this study, the structural formula of phuralumite, previously reported as Al2[(UO2)3(PO4)2(OH)2](OH)4(H2O)10, must be modified to Al2[(UO2)3(PO4)2O(OH)](OH)3(H2O)9.
Keywords: phuralumite; crystal structure; aluminium; uranyl phosphate; Kobokobo; formula revision